One Science Teacher's Professional Development Experience: A Case Study Exploring Changes in Students' Perceptions of Their Fluency with Innovative Technologies - Ebenezer, Jazlin; Columbus, Russell; Kaya, Osman Nafiz; Zhang, Lin; Ebenezer, Devairakkam Luke (Springer, 2012)
The purpose of this case-study is to narrate a secondary science teacher's experience of his professional development (PD) education and training in innovative technologies (IT) in the context of engaging students in environmental research projects The sources from which the narrative is derived include (1) the science teacher's reflective reports during three summer institute programs and (2) the science teacher's reflective reports while subsequently engaging students in IT-embedded environmental research projects in his classroom. The science teacher's explanations for changes in students' perception of their IT fluency illuminate his personal narrative. The science teacher attributed his growth and significant changes in students' perceptions of their IT fluency to the following mechanisms: (a) a personal commitment to developing his own and his students' IT abilities in the context of doing environmental research projects, and (b) an increase in class time devoted to science education due to school-time scheduling policy. The study implies that immersive professional development opportunities have the potential to produce significant increases in students' perceptions of their IT fluency.
Keywords: Professional development; Environmental research projects; Teacher's IT abilities; GIS technology